A CROSS SECTIONAL STUDY OF PREVALENCE OF METABOLIC SYNDROME (AS PER DEFINITION OF NCEP-ATP3) IN PATIENTS ATTENDING TERTIARY CARE HOSPITAL IN COAL - CAPITAL OF INDIA, DHANBAD - Dr. Neelam Agrawal,; Dr. Ruchi Shree,; Dr. Mahto Hemanti Raghu,; Dr. S.K. Verma, (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: This study was conducted to ascertain the prevalence of metabolic syndrome in patients undergoing treatment at a tertiary care facility in Dhanbad, India's coal capital, as determined by the NCEP-ATP III criteria.Methods: Over the course of July to November, a cross-sectional observational study was carried out in Shaheed Nirmal Mahato Medical College, Dhanbad. Consecutive sampling was used to enroll 300  patients (≥18 years old) who were enrolled in both inpatient and outpatient departments. A pre-tested structured questionnaire, physical examination, and laboratory studies were used to gather data on sociodemographic, clinical, and biochemical parameters. The NCEP-ATP III criteria were used to diagnose metabolic syndrome. SPSS was used for the statistical analysis, and a p-value of less than 0.05 was deemed statistically significant.Result: 32.7% of people had metabolic syndrome overall. Of the participants in the study, 46.7% were women and 53.3% were men. Females had a significantly higher prevalence (38.6%) than males (27.5%) (p=0.04). As people aged, the prevalence rose, reaching 52.2% in those over 60 (p